FACTORS INFLUENCING THE VOYAGE TIME OF A MARITIME VESSEL - Вишневський, Дмитро; Вишневська, Ольга (SWorldJournal, 2025)
This article examines a range of factors that play important role in a seagoing of vessel’s voyage. It was noted that voyage time includes both time at port and time at sea. Factors influencing time at port and time at sea were examined. It was also esta